Our inner conflicts : a constructive theory of neurosis - Horney, Karen, 1885-1952 (Routledge, 1999)
Annotation Routledge is now re-issuing this prestigious series of 204 volumes originally published between 1910 and 1965. The titles include works by key figures such asC. G. Jung, Sigmund Freud, Jean Piaget, Otto Rank, James Hillman, Erich Fromm, Karen Horney and Susan Isaacs. Each volume is available on its own, as part of a themed mini-set, or as part of a specially-priced 204-volume set. A brochure listing each title in theInternational Library of Psychologyseries is available upon request.
Keywords: Neuroses.; Psychology, Pathological.; Psychoanalysis.; Neurotic Disorders; Psychopathology; Psychoanalysis; Psychoanalytic Theory; Névroses.; Psychopathologie.; Psychanalyse.; psychoanalysis.; HEALTH & FITNESS -- Diseases -- General.; MEDICAL -- Clinical Medicine.; MEDICAL -- Diseases.; MEDICAL -- Evidence-Based Medicine.; MEDICAL -- Internal Medicine.; Neuroses; Psychology, Pathological; Samfundsvidenskab -- Psykologi.